May Measurement Month 2019: an analysis of blood pressure screening results from Pakistan-South Asia. (20th May 2021) - Memon, Feroz; Beaney, Thomas; Clarke, Jonathan; Ishaq, Mohammad; Bai, Kavita
Abstract: High blood pressure (BP) is well recognized as a huge health problem worldwide and is often described as a silent killer. To develop awareness and screening of this health issue globally, the International Society of Hypertension created 'May Measurement Month (MMM)' a campaign to provide BP screening and advice to interested participants. This screening and awareness campaign in Pakistan is a continuation of the efforts of the first MMM programme in Pakistan in 2017. This study was conducted in May and June 2019. This public based cross-sectional study included and screened 6919 individuals of either gender and aged ≥18 years, after informed consent. Information about prior diagnosis and treatment of hypertension with history about comorbidities and life-style were taken by a standard pre-designed form. Participants also asked about previous participation in MMM 2017/18. Arterial BP was measured using the OMRON digital BP apparatus and three successive readings were taken. Hypertension was defined as a systolic BP ≥140 mmHg or a diastolic BP ≥90 mmHg or taking antihypertensives. Participants had a mean age of 45.8 years and 47.1% had never had their BP checked. Of all those screened, 3601 (52.1%) participants had hypertension, of whom 56.2% were aware of their diagnosis, 49.5% were on antihypertensive medication and 19.8% had controlled BP (<140/90 mmHg). Of the 1783 participants on antihypertensive medication, 40.0% had controlled BP. In Pakistan, there are still low levels of awareness, counselling and screening about high BP. Further large-scale studies are required in this region to evaluate these problems and link them with potential solutions.